Protection of personal data of victims of child sexual abuse in court decision - Mansyur Mansyur; Yasser Arafat (Geuthèë Institute, Aceh, 2023)
This article was prepared with the intention of outlining legal protection for victims who are not anonymized in decisions on cases of child sexual intercourse and legal remedies that can be taken. The research method used is normative legal research with research data in the form of legal materials consisting of primary legal materials in the form of laws and regulations and all official documents containing legal provisions relating to research topics and secondary materials consisting of text books written by influential jurists, law journals, legal cases related to the research topic. The law material analysis technique used is logical deduction. The research approach used is a statutory, conceptual and case approach. The author concludes that the law provides protection to the aggrieved party due to negligence in obscuring the child's identity in court decisions published on the website of the Supreme Court decision directory in the form of threats of disciplinary sanctions and/or criminal sanctions. Sanctions are a form of preventive legal protection that makes people introspective so that they do not violate the law so that no party is harmed. The aggrieved party can submit an application to the Supreme Court through the District Court in order to obscure the identity of the party in the decision that has already been published. If the request is not followed up, then the aggrieved party can report to the Ombudsman.